ColEval: Honeybee COLony Structure EVALuation for Field Surveys - Hernandez, Julie; Maisonnasse, Albin; Cousin, Marianne; Beri, Constance; Le Quintrec, Corentin; Bouetard, Anthony; Castex, David; Decante, Damien; Servel, Elois; Buchwalder, Gerald; Brunet, Francois; Feschet-Destrella, Estelle; et al. (My University, 2020)
Methods for the evaluation and comparison of the structure of numerous honeybee colonies are needed for the development of applied and fundamental field research, as well as to evaluate how the structure and activity of honeybee colonies evolve over time. ColEval complements existing methods, as it uses an online reference image bank for (human) learning and training purposes. ColEval is based on the evaluation of the surface area percentage occupied by different components of a honeybee colony: adult worker bees, open and capped brood, honey, nectar, and pollen. This method is an essential tool for the description of the evolution in the size of honeybee colonies. The procedure makes allowances for tendencies between different observers and uses them to calculate accurate measurements of honeybee colony evaluation. ColEval thus allows for a posteriori comparison of under- or over-evaluation made by different observers working on the same project; it is thus possible to eliminate observer bias in the measurements and to conduct large surveys.
Keywords: honeybees; colony structure; field experiment; human estimations of colony hive